Design Web Based Ticketing System, for Menara Alor Star - Al-Nimrat, Mohammad Methkal Hassan (2009)
Web based is the most famous portable technology, the WEB solution services can be obtained easily at any time in anywhere. That provides the crowed with the ticket for visit the Menara without losing time and effort. Web based allows to the users to use the Information Technology without being bound to a single location; it provides the users with the flexibility. In this study focused only to the development of a prototype for the Menara Alor Star e-ticketing. Reservation system comprises of a database that is built using MySQL database application software, Apache server as the web server and JSP as its application server. The methodology used is General Methodology using the Unified Modeling Language-UA Approach.